The Role of Accounting Literacy and Internal Control in Maintaining Financial Information Quality: A Document Analysis Study of BPRS in Aceh Province - Laras Hijriani; Marjulin Marjulin; Busra Busra; Hismendi Hismendi (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2026)
The revocation of business licenses of three Islamic Rural Banks (BPRS) in Aceh Province within one year raises serious concerns about the quality of financial information generated by these institutions. This study examines the role of accounting literacy and internal control in maintaining financial information quality at BPRS in Aceh Province through a qualitative document analysis approach. Secondary data were collected from publicly available financial reports and supervisory documents published by Otoritas Jasa Keuangan (OJK) for the period 2020–2024. The analysis employs a disclosure scoring framework based on four qualitative characteristics: relevance, reliability, comparability, and timeliness. Findings indicate that BPRS with weaker accounting literacy indicators demonstrate lower disclosure completeness scores, while banks with documented internal control deficiencies exhibit greater variability in financial reporting quality. The study concludes that both accounting literacy and internal control play critical roles in sustaining financial information quality, and their deterioration may contribute to institutional failure in Islamic rural banking.